The 1866 Vercoe and Harding map and the axonometric: the object of subjective representation - O'Shaughnessy, Katherine (Architectural History Aotearoa, 2010)
The 1866 Vercoe and Harding map of Auckland provides a visual description of colonial development during the 1860s. This map is a static representation of the past and the backdrop to an exploration of the site via architectural drawing. This paper outlines the process of excavating a site through axonometric drawing looking specifically at an area within Freemans Bay. It explains how the two dimensional Vercoe and Harding map has been extruded into a three dimensional representation of the site. The idea of the map as a subjective representation of the past will be explored alongside the use of what might be considered an objective drawing type to create a subjective visualization of the site. The paper will investigate the process of creating this axonometric and the way in which this drawing relies on both historical fact and historical assumption. It will address how this process produces an understanding of the site, namely, the ability to translate each building based on the simple outline of its plan. This paper is part of a wider investigation into the documentation of heritage sites and the use of drawing to create an understanding of place. Thus, this drawing alone does not create this awareness of place, but rather, informs a new understanding of the 1866 map and a representation of what Freemans Bay might have been during the 1860s. At first glance, it might seem that a map is objective. It is a tool traditionally used for navigation and thus reliant upon objectivity. We generally trust that the person creating the map has provided us with the accurate details of the area we are navigating. We are here and the map maker can tell us how to get there. Therefore, we trust, that the 1866 Vercoe and Harding map of Auckland will provide us with a glimpse of life in Auckland during the 1860s. It might also seem that an axonometric is objective. This method of drawing is scaled and measured; it represents a three-dimensional object upon a two-dimensional surface. A plan can be extruded with the knowledge provided by the object's elevations to portray an objective, measured representation of the object. This paper investigates the seemingly objective map and axonometric through the extrusion of a portion of Vercoe and Harding's 1866 map of Auckland into an axonometric drawing. When the map is extruded into an axonometric drawing, the subjective qualities of both are revealed. In creating a new axonometric projection of a map, questions arise, such as: why the document was made? what was being represented? and how much is this document reliant upon the views of those who made the map? Equally, the subjective nature of the axonometric drawing is revealed through this process of extruding the map. For example, without a comprehensive and complete record of the site, the drawing is reliant upon a number of assumptions and these assumptions are dependent upon the subjective view of the axonometer. Therefore, the axonometric drawing derived from the map is a supposedly objective document reliant on the subjective. The axonometric drawing derived from the 1866 Vercoe and Harding map of Auckland is part of a larger project which attempts to document place by revealing the possible history of a site. A range of maps are considered in this project, all being extruded in the same manner as the Vercoe and Harding map but each having its own process dependent on the time the map is representing. These axonometric projections of various maps, together, aim to represent both time and space and to convey a sense of place.